Transcriptomic profiling reveals SARS-CoV-2-infected humanized MHC mice recapitulate human post vaccination immune responses - Li, Siyue; Han, Xuelian; Hu, Ruolan; Sun, Keyu; Li, Min; Wang, Yuan; Zhao, Guangyu; Li, Mengzhe; Fan, Huahao; Yin, Qi (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundThe ongoing COVID-19 pandemic caused by SARS-CoV-2 remains a critical global health priority, with persistent socioeconomic ramifications despite its reclassification from Public Health Emergency of International Concern (PHEIC) status. While humanized major histocompatibility complex (hMHC) murine models have been extensively utilized in oncological research, their application in virological studies-particularly for coronavirus pathogenesis-remains underexplored. MethodsThis study systematically characterized immune responses in SARS-CoV-2-challenged hMHC mice lung tissues through comparative transcriptomic profiling, combined with functional enrichment and PPI network analyses.ResultsKey findings demonstrate that hMHC mice exhibit enhanced immunological activation relative to wild-type controls, particularly in IFN-γ signaling pathways and neutrophil mobilization dynamics that closely parallel human post-vaccination responses. Comparative analysis with human whole blood RNA-seq datasets revealed that hMHC mice exhibit both high reproducibility in transcriptomic profiles and significant similarity to human immune responses across innate and adaptive immunity. ConclusionsThese results confirm that the hMHC murine model can serve as an effective platform for vaccine research, providing a theoretical foundation for the application of humanized MHC mice and offering new insights into viral infection mechanisms and the development of novel vaccines.